FORMATION PRINCIPLES OF THE ORGANIZATIONAL AND ECONOMIC MANAGEMENT MECHANISM OF THE REGIONAL ENTERPRISE’S CREATIVE POTENTIAL - N. Zakharchenko; S. Horbachenko; R. Hrinchenko; I. Topalova; A. Fialkovska (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. Purpose of the study — to provide theoretical and methodological substantiation of construction of organizational and economic management mechanism of creative potential of the region tourist company taking into account influence of factors of modern culture. The article presents theoretical, methodological and practical principles for building and implementing organizational and economic mechanism for managing the creative potential in the region, taking into account the current level of corporate culture. The solution to this problem is achieved by identifying the characteristics and principles of organizational and economic mechanism for assessing the creative potential of the region on the example of a travel company, for which the appropriate mechanism is built. The article substantiates the development of a comprehensive methodology for quantitative assessment of the creative potential of a travel company, which made it possible to determine their potential ability to introduce new products in the tourism business of the region. An effective condition for the introduction of such a technique in practice is the need for periodic use of both quantitative and qualitative approaches to the object of study in the process of in-depth study of its creative potential. Effective management of creative potential increases the company’s ability to market innovative services. Scientific novelty of introduction of the organizational and economic mechanism of management of creative potential of the enterprise in the region taking into account achievement of a modern corporate culture level.